Hyaluronic acid covers in burn treatment: a systematic review - Michel Marcos Dalmedico; Marineli Joaquim Meier; Jorge Vinícius Cestari Felix; Franciele Soares Pott; Francislene de Fátima Cordeiro Petz; Michelle Caroline Santos (SciELO, 2016)
Abstract OBJECTIVE To evaluate the effectiveness of hyaluronic acid in the healing of partial thickness burns. METHOD Systematic review of randomized controlled trials on the use of hyaluronic acid for the topical treatment of skin burns, based on recommendations of the Cochrane Handbook for Systematic Reviews of Interventions. RESULTS Two randomized controlled trials that analyzed 143 patients with partial thickness burns and/or deep partial thickness burns were selected. They compared the application of hyaluronic acid 0.2% associated to silver sulfadiazine 1% 5g/cm2 versus silver sulfadiazine 1% 5g/cm2 alone for the outcome of complete healing. CONCLUSION This review emphasizes the need for new well-designed randomized controlled trials to establish the therapeutic relevance of hyaluronic acid with respect to the healing of burns of partial thickness or deep partial thickness.